On M. G. Krein’s works in the theory of representations and harmonic analysis on topological groups - Vainerman, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
This is a brief survey of M. G. Krein’s papers in the theory of representations and harmonic analysis on topological groups. These papers are known to be classical and form the basis of numerous contemporary researches into these fields.